148k views
5 votes
-10 4/7 - (-3)
- 10 (4)/(7) ( - 3)

-10 4/7 - (-3)- 10 (4)/(7) ( - 3)-example-1
User PArt
by
5.2k points

1 Answer

0 votes

The following expression:


-10(4)/(7)-(-3)

Can be rewritten using some notation for mixed fractions. Remember that:


-10(4)/(7)=-10-(4)/(7)

Then:


-10(4)/(7)-(-3)=-10-(4)/(7)-(-3)

Use the commutative property of the sum to bring together the integer part of the expression:


-10-(4)/(7)-(-3)=-10-(-3)-(4)/(7)

Notice that -(-3) = +3, then:


-10-(-3)-(4)/(7)=-10+3-(4)/(7)

Add the integers:


-10+3-(4)/(7)=-7-(4)/(7)

Rewrite the number as a mixed fraction:


-7-(4)/(7)=-7(4)/(7)

Therefore:


-10(4)/(7)-(-3)=-7(4)/(7)

User MichaelM
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.